Co-movement and dependency between New York Stock Exchange, London Stock Exchange, Tokyo Stock Exchange, oil price, and gold price - Pathairat Pastpipatkul (2018)
© Springer International Publishing Switzerland 2015. This paper aims to analyze the co-movement and dependence of three stock markets, oil market, and gold market. These are gold prices as measured by gold future, crude oil prices as measured by Brent, and stock prices as measured by three developed stock markets comprising the U.S. Dow Jones Industrial Average, the London Stock Exchange, and the Japanese Nikkei 225 index. To capture the correlation and dependence, we employed the application of C-vine copula and D-vine copula. The results demonstrate that the C-vine copula is a structure more appropriate than the D-vine copula. In addition, we found positive dependency between the London Stock Exchange and the other markets; however, we also obtained complicated results when the London Stock Exchange, the Dow Jones Industrial Average, and Brent were given as the conditions. Finally, we found that gold might be a safe haven in this portfolios.